2012
DOI: 10.1103/physrevb.86.060505
|View full text |Cite
|
Sign up to set email alerts
|

Linewidth dependence of coherent terahertz emission from Bi2Sr2CaCu2Oet al.

Abstract: We report on measurements of the linewidth ∆f of THz radiation emitted from intrinsic Josephson junction stacks, using a Nb/AlN/NbN integrated receiver for detection. Previous resolution limited measurements indicated that ∆f may be below 1 GHz -much smaller than expected from a purely cavity-induced synchronization. While at low bias we found ∆f to be not smaller than ∼ 500 MHz, at high bias, where a hotspot coexists with regions which are still superconducting, ∆f turned out to be as narrow as 23 MHz. We att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 52 publications
4
86
3
Order By: Relevance
“…5,6 Furthermore, it is possible that hot spots form a shunt between the stacked Josephson junctions, thereby promoting their synchronization. 5,11 This is consistent with studies, which find a narrower THz radiation line width from mesas with comparatively high DC power dissipation. 12 Furthermore, it was observed that mesas covered with thick electrodes that homogenize the temperature do not emit THzradiation.…”
Section: Introductionsupporting
confidence: 80%
“…5,6 Furthermore, it is possible that hot spots form a shunt between the stacked Josephson junctions, thereby promoting their synchronization. 5,11 This is consistent with studies, which find a narrower THz radiation line width from mesas with comparatively high DC power dissipation. 12 Furthermore, it was observed that mesas covered with thick electrodes that homogenize the temperature do not emit THzradiation.…”
Section: Introductionsupporting
confidence: 80%
“…To accommodate multiple fluxons and achieve a flux-flow regime, the length of the Josephson junction used as a FFO exceeds the Josephson penetration length by a large factor. The potential of FFO for practical applications has been justified by development of a superconducting integrated receiver (SIR) [65,66] which was successfully used in remote heterodyne spectroscopy of the Earth atmosphere on board of a high-altitude balloon [67,68], as well as first spectral measurements of THz radiation emitted from intrinsic Josephson junction stacks (BSCCO mesa) at frequencies up to 750 GHz [69,70].…”
Section: Model Of Josephson Flux-flow Oscillatormentioning
confidence: 99%
“…The THz emission properties of the IJJ stacks are affected by the hot spot. For example, it has been found that the linewidth of radiation is much narrower in the high-bias regime than at low bias 12,60 . Other properties such as the emission frequency seem to be basically independent of the hot spot position, leading to some debate as to whether the hot spot is helpful for radiation or just coexists with the radiating regions 20,22,23 .…”
Section: Introductionmentioning
confidence: 99%